Climate change in reclamation landscapes – Adaptation between module and modularity - Carla Brisotto; Jeff Carney; Ina Macaione; Alessandro Raffa (Agathón)
Modern drainage of wetlands has produced landscapes that are expressions of a productive view of natural space. These landscapes result from a profound environmental transformation driven by economic, social, health, and cultural reasons. Today, these autonomous territorial machines face the effects of climate change, a challenge that will require significant changes and a paradigm shift leading to new ecologies and aesthetics. Through an unexplored comparison of reclamation landscapes between the Everglades, Florida (US) and Metaponto, Basilicata (Italy), this contribution reflects on the limits and possibilities of adaptation through the concepts of module and modularity. The emerging themes will inform future methodological and operational experimentations for adapting modern reclamation landscapes to climate change.